Formation of information culture of personality in the process of teaching mathematics within the discipline «managerial methods of decision making» - M V Morozova (RUDN Journal of Informatization in Education, 2012)
This article contains structural elements of the methodology for formation of personal information culture in the study of mathematics for the specialty «State and municipal management» (on the subject «Methods of decision-making»).